2012
DOI: 10.1038/ncomms1697
|View full text |Cite
|
Sign up to set email alerts
|

Host factors dictate control of viral replication in two HIV-1 controller/chronic progressor transmission pairs

Abstract: Viremic controllers (VC) and elite controllers/suppressors (ES) maintain control over HIV-1 replication. Some studies suggested that control is a result of infection with a defective viral strain while others suggested host immune factors play a key role. Here we document two HIV-1 transmission pairs: one consisting of a patient with progressive disease and an individual who became an ES, and the second consisting of a patient with progressive disease and a VC. In contrast to another ES transmission pair, viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 56 publications
1
50
1
Order By: Relevance
“…Full-genome sequence analysis and phenotypic analyses have suggested that these isolates are fully pathogenic [4] and in a proof of concept study, virus cultured from ECs were shown to replicate vigorously and induce CD4 + T-cell depletion in humanized mice [7]. Transmission studies between patients with progressive disease (chronic progressors [CPs]) and ECs [8,9] have also suggested that some of these patients are infected with replication-competent virus and in one case, it appears that an EC transmitted virus to a CP [9]. Finally, some ECs develop virologic progression over time [10] and an EC was shown to develop viremia after chemotherapy [11].…”
Section: The Presence Of Replicationcompetent Virus In Elite Controllersmentioning
confidence: 99%
“…Full-genome sequence analysis and phenotypic analyses have suggested that these isolates are fully pathogenic [4] and in a proof of concept study, virus cultured from ECs were shown to replicate vigorously and induce CD4 + T-cell depletion in humanized mice [7]. Transmission studies between patients with progressive disease (chronic progressors [CPs]) and ECs [8,9] have also suggested that some of these patients are infected with replication-competent virus and in one case, it appears that an EC transmitted virus to a CP [9]. Finally, some ECs develop virologic progression over time [10] and an EC was shown to develop viremia after chemotherapy [11].…”
Section: The Presence Of Replicationcompetent Virus In Elite Controllersmentioning
confidence: 99%
“…CD8 ϩ T cells from ES maintain a polyfunctional response after stimulation with HIV-1 peptides (2,5,17), and there is significantly higher expression of granzyme B and perforin by HIV-1-specific CD8 ϩ T cells from ES than from CP (24,36,37). In addition, CD8 ϩ T cells from ES are much more effective at suppressing HIV-1 replication in autologous CD4 ϩ T cells in vitro than CD8 ϩ T cells from CP (3,7,13,37,48,49), and the inhibitory potential of CD8 ϩ T cells has recently been shown to be predictive of the rate of CD4 ϩ T cell decline early in viral infection (57). Current analysis of the CD8 ϩ T cell response in HIV-1 infection has focused primarily on unfractionated populations of CD8 ϩ T cells.…”
mentioning
confidence: 99%
“…While some studies have suggested that some ES are infected with attenuated or defective virus, others have shown that some ES are infected with replication-competent virus. We have documented the transmission of replication-competent HIV-1 isolates from CPs to ES (16,18), and studies have shown persistent viremia in ES (51-53), evolution of plasma virus over time (54)(55)(56), and a decrease in the frequency of latently infected CD4 ϩ T cells in ES treated with highly active ART (HAART) (57). However, other studies comparing individual viral proteins from ES and CPs have reported reduced fitness of ES Gag (10, 58), Env (59), reverse transcriptase (60), and Nef (61) proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies, replication-competent HIV-1 isolates were cultured from some ES (13)(14)(15), and full-genome sequence analysis of these replication-competent isolates did not reveal any large deletions or signature mutations (13). It has been very challenging to isolate virus from ES, and full-length genotypic analyses have been performed on replication-competent isolates obtained from fewer than 10 ES (11,13,(16)(17)(18) and just 3 HLA-B‫-75ء‬positive ES (13,16,18). Furthermore, studies comparing the growth kinetics of replication-competent virus from ES to those of multiple isolates from patients with progressive disease have not been performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation